2010
DOI: 10.1094/pdis-04-10-0276
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Bacterium and Yeasts Associated with Pineapple Fruit Collapse in Espírito Santo State, Brazil

Abstract: In rainy and warm periods of the year, after a dry, hot season (December/March), commercially grown pineapple (Ananas comosus var. comosus) in Espírito Santo State, Brazil has been affected by fruit collapse disease with significant commercial losses (15 to 20%) each year. Symptoms include intense flesh fermentation, spontaneous exudation of liquid and froth, and ripe inner fruit tissue deterioration on plants and postharvest. Isolation of microorganisms of diseased fruits on nutrient agar, potato dextrose aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…(Kaneshiro et al, 2008). However, Korres et al (2010) from Brazilia suggested that pineapple fruit collapse was caused by Klesiella sp. in combination with yeasts.…”
Section: Results and Dissccusionmentioning
confidence: 99%
“…(Kaneshiro et al, 2008). However, Korres et al (2010) from Brazilia suggested that pineapple fruit collapse was caused by Klesiella sp. in combination with yeasts.…”
Section: Results and Dissccusionmentioning
confidence: 99%
“…Fruit collapse and bacterial heart rot are common diseases in pineapples' low-acid hybrids. In countries such as Malaysia, Brazil, and Indonesia, fruit collapse has recently been recorded (Rohrbach and Johnson 2003;Korres et al 2010;Prasetyo and Aeny 2014). Fruit collapse, a disease that has never been identified before 2014 in Indonesia, causes the fruits got rotten and collapsing immediately three to two weeks close to fully ripening, resulting in considerable losses by 50% suffered by the plantation (Peckam et al 2010;Prasetyo and Aeny 2014;Sueno et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…pneumoniae has received much attention due to an association with human and animal diseases [5, 6]. Additionally, it not only has been isolated from plants including spinach [7] and rice [8] but also has recently been implicated in a disease of pineapple (pineapple fruit collapse) [9]. It is unclear how one species could be so successful on such different substrates as fruit and human tissue that it could cause disease symptoms in both.…”
Section: Introductionmentioning
confidence: 99%